Strategie komunikacyjne w obliczu trudności językowych - Morytz, Jolanta (Neofilolog, 2017)
Foreign language classes at university should enhance not only knowledge of foreign languages but with the use of different methods, should also develop skills of communication strategies, which are very important to compensate for deficits in communication. These strategies are indispensable for language learners irrespective of their level of proficiency. The objective of the study described in the present paper is to explore the communication strategies used by Polish students at different levels of knowledge of Italian. Data was collected by two types of questionnaires, one including two open-ended questions. The other was based on a Likert-scale method which examined the frequency of usage of avoidance strategies, verbal and non verbal strategies, as well as the strategy of transfer. Emphasis was placed on the relationship between the use of types of communication strategies and students’ level of proficiency. In the final part the author recommends types of lexical exercises which should be practised during classes to help students to develop their communicative skills.